2017
DOI: 10.1021/acs.jpclett.7b00313
|View full text |Cite
|
Sign up to set email alerts
|

On the Charge State of Titanium in Titanium Dioxide

Abstract: The oxidation state of titanium in titanium dioxide is commonly assumed to be +4. This assumption is used ubiquitously to rationalize phenomena observed with TiO 2 . We present a comprehensive electronic structure investigation of Ti ions, TiO 2 molecules and TiO 2 bulk crystals, using different density functional theory and wave function-based approaches, which suggests a lower oxidation state (+3). Specifically, there is evidence of a significant remaining contribution from valence s and d electrons of Ti, i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 54 publications
(103 reference statements)
18
67
0
Order By: Relevance
“…It has been suggested that the different charges between Ti and bacterial cell wall may act as an ionic bonding coaggregation, as cell membranes are essentially composed by negatively charged lipids 32 and TiO 2 layer formed on Ti material implants is positively charged. 33 Coupled with that, The main strength of this study is to be the first one to provide the experimental evidence on the effect of Ti products in modulating an in situ biofilm to a dysbiotic state. These results may guide future studies in the field, as they suggest a possible role for Ti products in the etiopathogenesis of peri-implantitis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It has been suggested that the different charges between Ti and bacterial cell wall may act as an ionic bonding coaggregation, as cell membranes are essentially composed by negatively charged lipids 32 and TiO 2 layer formed on Ti material implants is positively charged. 33 Coupled with that, The main strength of this study is to be the first one to provide the experimental evidence on the effect of Ti products in modulating an in situ biofilm to a dysbiotic state. These results may guide future studies in the field, as they suggest a possible role for Ti products in the etiopathogenesis of peri-implantitis.…”
Section: Discussionmentioning
confidence: 92%
“…The mechanisms by which Ti particle and ions increase bacteria growth are still unknown. It has been suggested that the different charges between Ti and bacterial cell wall may act as an ionic bonding coaggregation, as cell membranes are essentially composed by negatively charged lipids and TiO 2 layer formed on Ti material implants is positively charged . Coupled with that, the dose‐dependent effect from Ti ions on the significant increase of anaerobic periodontal pathogens suggests a direct effect from Ti ions high oxygen vacancies, whose excess electrons transitions from Ti 3+ excited states to the occupied reduced TiO 2 states, thus reducing the O 2 availability in the biofilm microenvironment and favoring the shift of the microbial community toward specific anaerobic bacteria species.…”
Section: Discussionmentioning
confidence: 99%
“…Fig. 2 shows the average C-O stretch frequencies (without considering degeneracies) versus the assumed CO ligand charges (with assumed fixed +2 charge state of Fe) for [Fe(CO) 4 ] 2-(q CO = -1 |e|), Fe(CO) 5 (q CO = -0.4 |e|) and [Fe(CO) 6 ] 2+ (q CO = 0 |e|) calculated with DFT. Although the experimentally observed frequencies could not be matched accurately (overestimation on the order of 100 cm -1 (7 %)), which might be caused by non-vacuum frequency values used in the data basis of ref.…”
Section: 2mentioning
confidence: 99%
“…While formal oxidation states are derived from orbital occupancies, the electron density is a physical observable and its local change can be directly related to electron fluxes into and out of a certain volume element and can therefore help rationalize the direction of electron transfers, which formal oxidation states often fail to represent. We showed this mismatch by a detailed charge density analysis in TiO2 molecules and crystals from which we concluded that there is still a substantial charge remainder on Ti in titanium dioxide [32,33], which is, although not formally conflicting with a +4 oxidation state, a rather counter-intuitive observation and in principle allows for electron density transfers away from Ti or In our work, we used both plane wave and localized basis sets. We were able to achieve good agreement between them when tuning localized basis sets of small size (DZP) to reproduce cohesive energies of components (such as bcc Li, diamond Si etc.).…”
Section: Discussionmentioning
confidence: 84%
“…In [32,33], we analyzed the charge state (and from there oxidation state) of Ti in TiO 2 . Titanium dioxide is by far the most prominent oxide that found use in multiple electrochemical power generation and storage technologies such as solar cells (dye-sensitized and sensitized-type perovskite) and batteries (including post-lithium batteries considered here) as well as in photocatalysis for environmental remediation and water splitting [39,[101][102][103][104][105][106][107]110,112].…”
Section: On the Charge And Oxidation State Of Titanium In Tiomentioning
confidence: 99%